A 1.2 T canted cosθ dipole magnet using high-temperature superconducting CORC® wires. (21st May 2019) - Wang, Xiaorong; Dietderich, Daniel R; DiMarco, Joseph; Ghiorso, William B; Gourlay, Stephen A; Higley, Hugh C; Lin, Andy; Prestemon, Soren O; Laan, Danko van der; Weiss, Jeremy D
Abstract: REBa2 Cu3 O x (REBCO, RE = rare earth elements) coated conductors can carry high current in high background fields, in principle enabling dipole magnetic fields beyond 20 T. Although model accelerator magnets wound with single REBCO tapes have been successfully demonstrated, magnet technology based on high-current REBCO cables for high-field accelerator magnet applications has yet to be established. We developed a two-layer canted cos θ dipole magnet with an aperture of 70 mm using 30 m long commercial Conductor on Round Core (CORC ® ) wires. The 3.1 mm diameter CORC ® wire contained 16 commercial REBCO tapes with a 30 μ m thick substrate. The magnet was tested at 77 and 4.2 K. It generated a peak dipole field of 1.2 T with 4.8 kA at 4.2 K with neither thermal runaway nor training. Reasonable geometric field quality and strong magnetization-current effects with multipole decay were observed. Our work demonstrated a feasible high-temperature superconducting magnet technology as a first step toward a new accelerator magnet paradigm that will enable high-field inserts for next-generation circular colliders and stand-alone magnets that can operate over a wide temperature range for a broad range of applications.